Penerapan Excellence Management System pada Pengelolaan Aset Kendaraan di PT SPIL - Davin Tandy; I Gede Agus Widyadana (Jurnal Titra, 2021)
Company assets are important for every company because assets are one of the property owned by the company. Asset management will improve the company’s finances through efficient and optimal use of assets, planning for asset purchases or investments, and increase asset security. PT SPIL also manages vehicle assets such as vehicle maintenance, vehicle documents renewal, and vehicle movement between locations. PT SPIL performs asset management manually which causes several problems, such as time wasted recording asset variables, disorganized data, prone to incorrect records, and difficulty in finding past data. Manual asset management problems can be minimized by digitizing asset management. The digitization of asset management can be in the form of implementing an asset management information system. This system is designed to perform automatic and integrated asset updates, provide asset management reminder notifications, and store asset management data. With this system, PT SPIL can extend vehicle documents without delay resulting in unnecessary sanctions, can take better care of the vehicle so that the vehicle has a longer life cycle, and avoid miscommunication between the core and branches.